MODERN DIAGNOSTIC AND THERAPEUTIC TECHNOLOGIES FOR THE CHEST TRAUMA ASSOCIATED WITH THE FALL FROM A HEIGHT IN THE REPUBLIC RESEARCH CENTRE OF EMERGENCY MEDICINE - A. M. Khadzhibayev; P. K. Sultanov; R. O. Rakhmanov (Неотложная медицинская помощь)
BACKGROUND. The rate of the multisystem chest trauma and mortality in patients with catatrauma remains high.OBJECTIVE. To study the diagnosis and treatment of the multisystem chest trauma in patients associated with the fall from a height.MATERIAL AND METHODS. 243 patients (208 multisystem injuries and 35 isolated injuries) with a chest trauma associated with the fall from a height were examined in the surgical department of Republic research centre of emergency medicine. We performed X-ray, CT and endosurgical examinations.RESULTS. Instrumental examination revealed pneumothorax and hydrothorax in 24.4% and 22.6% of victims respectively. The rib injuries were observed in 181 patients, sternum fractures in 8 victims and thoracic vertebrae fractures in 84 patients. The puncture and thoracocentesis of the pleural cavities were performed in 85 cases. The thoracoscopy was performed in 21 patients, the thoracotomy – in 15 patients, suturing of the lung – in 22 patients, coagulation – in 15 patients, external plate fixation of multiple injured ribs – in 10 patients. The mortality rate was 21.4%.CONCLuSION. The specifics of the multisystem chest trauma associated with the fall from a height is the development of hemothorax and pneumothorax. Thoracocentesis and videothoracoscopy allow to diagnose and stop the hemorrhage properly, to restore the lung rupture and perform the thoracotomy in severe cases, as well as reduce of complications frequency and mortality rate.